Assessing the reliability and responsiveness of the SF-6Dv2 and comparing its validity to the EQ-5D-5L among colorectal cancer patients in China - Sun, Jiannan; Xu, Lijun; Cao, Yiyin; Shi, Jiaxuan; Wang, Yujin; Wu, Lemin; Yu, Hongjuan; Liu, Jiazhuo; Huang, Weidong (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the reliability and responsiveness of the SF-6Dv2, and to provide the first comparative assessment of its validity against the EQ-5D-5L in Chinese patients with colorectal cancer (CRC).MethodsA cross-sectional survey was conducted between August 2022 and December 2023 in three tertiary hospitals in Harbin, China. Eligible CRC patients completed face-to-face baseline interviews to collect demographics, health behaviors, clinical characteristics, EQ-5D-5L, and SF-6Dv2. Follow-up surveys were administered at 7 days and 3 months to collect self-reported health changes and SF-6Dv2. Ceiling and floor effects were assessed by calculating the proportion of respondents reporting the best and worst possible health states. Convergent validity was assessed using Spearman’s correlation with EQ-5D-5L as the reference. Known-groups validity was examined by comparing utility scores across groups categorized by health behaviors and clinical characteristics, testing effect size (ES) and relative efficiency (RE). Agreement was examined using intraclass correlation coefficients (ICC) and Bland-Altman plot. Test-retest reliability of SF-6Dv2 utility and dimension scores was evaluated using ICC and Gwet’s AC over 7 days. Responsiveness was assessed using standardized response mean (SRM) over 4 months.ResultsBaseline included 287 CRC patients; 131 and 111 completed first and second follow-ups. A higher ceiling effect was observed in EQ-5D-5L than in SF-6Dv2 (16.7% vs 3.1%). The Spearman correlation between EQ-5D-5L and SF-6Dv2 utility scores was 0.716 (dimensions: 0.313-0.675). Utility scores from EQ-5D-5L and SF-6Dv2 showed moderate agreement (ICC = 0.686). SF-6Dv2 showed superior known-groups validity in surgical treatment (RE = 1.796) and ECOG groups (RE = 1.953). SF-6Dv2 demonstrated excellent test-retest reliability for utility scores (ICC = 0.866), with Gwet’s AC across dimensions (0.322-0.669). SF-6Dv2 showed greater responsiveness in the worsened group (SRM = 0.788) compared to the improved group (SRM = 0.687).ConclusionsSF-6Dv2 showed comparable reliability and responsiveness when used in patients with CRC, out-performing EQ-5D-5L in differentiating clinical known-groups and showing promise for cancer practice and research.